2012
DOI: 10.3109/07853890.2011.583674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic training on hot flushes and quality of life—a randomized controlled trial

Abstract: Background and objective. To estimate whether aerobic training has an effect on frequency of hot flushes or quality of life.Design. A randomized controlled trial.Participants and setting. Symptomatic, sedentary women (n = 176), 43–63 years, no current use of hormone therapy.Intervention. Unsupervised aerobic training for 50 minutes four times per week during 6 months.Outcomes. Hot flushes as measured with Women's Health Questionnaire (WHQ) and Health-Related Quality of Life (HRQoL, SF-36), daily reported hot f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 35 publications
(42 reference statements)
6
100
0
12
Order By: Relevance
“…Women with BMI scores in the normal range had lower vasomotor symptom scores and better health-related QOL scores than obese women, and those who gained weight were more likely to report deterioration in their QOL (25). We found that women with a normal BMI had a significantly lower total MRS score compared with underweight, overweight or obese women and this is consistent with another previous study (26).…”
Section: Discussionsupporting
confidence: 82%
“…Women with BMI scores in the normal range had lower vasomotor symptom scores and better health-related QOL scores than obese women, and those who gained weight were more likely to report deterioration in their QOL (25). We found that women with a normal BMI had a significantly lower total MRS score compared with underweight, overweight or obese women and this is consistent with another previous study (26).…”
Section: Discussionsupporting
confidence: 82%
“…Moderate physical activity was associated with decreased objective and subjective hot flashes 24 hours post exercise [46], although worse reported symptoms were reported in women with lower fitness levels. In a randomised controlled trial, 176 symptomatic sedentary women who were given an aerobic exercise regime 50 minutes 4x per week over 6 months, reported a decrease in the frequency of hot flashes [47]. In 3,201…”
Section: Benefits To Vasomotor Symptomsmentioning
confidence: 99%
“…Destaca-se também a influência positiva da atividade física na qualidade de vida das mulheres no climatério nos estudos de coorte e prospectivo. [17][18][19][20][21][22][23][24] Com relação à avaliação metodológica dos artigos desta revisão, verificou-se entre os estudos que realizaram intervenção, ocorreu uma variação de escore entre 13 a 21 pontos com uma média de 57,75 pontos. Quanto aos estudos que não tiveram intervenção, observou-se uma variação de escore entre 12 a 15 pontos com média de 90,14 pontos.…”
Section: Figura 1 Fluxograma Da Seleção Dos Estudos De Acordo Com Asunclassified